The Influence of Work Motivation and Work Discipline on the Performance of Public Elementary School Teachers - Astria Ningsih; Tri Widayatsih; Mahasir Mahasir (Yayasan Sembilan Pemuda Indonesia, 2026)
This study aims to analyze the combined influence of work motivation and work discipline on the performance of elementary school teachers in Rantau Bayur District. Employing a quantitative descriptive method, data were collected via questionnaires, observation, and documentation from a sample of 95 teachers and principals across 10 public elementary schools. Statistical analysis included normality, linearity, and multicollinearity tests, followed by correlation, regression, t-tests, and an F-test. The results demonstrate that both factors significantly and positively affect teacher performance, with their combined influence being substantially greater than their individual effects. The novelty of this research lies in its focused examination of the synergy between intrinsic motivation and behavioral discipline within a specific rural Indonesian educational context. A key practical implication is the need for school administrators to develop integrated policies that simultaneously enhance motivational incentives and reinforce disciplinary frameworks. This study contributes actionable empirical evidence to the field of educational management, highlighting that holistic human resource strategies, rather than isolated interventions, are critical for optimizing teacher performance in public elementary schools.